Электромиографические проявления наследственных признаков экстрапирамидной недостаточности - Луханина, Е.П.; Карабань, И.Н.; Чивликлий, М.А.; Пилькевич, Н.А.; Березецкая Н.М. (Нейрофизиология, 2010)
У клинически здоровых родственников пациентов, страдающих болезнью Паркинсона (БП), изучали амплитудные и частотные характеристики ЭМГ-активности сгибателей и разгибателей локтевого сустава, стараясь выявить у этих лиц признаки экстрапирамидной недостаточности (ЭПН) и предложить рекомендации для подобной группы риска. У клінічно здорових родичів пацієнтів із хворобою Паркінсона (ХП) вивчали амплітудні та частотні характеристики ЕМГ-активності згиначів і розгиначів ліктьового суглоба, намагаючись виявити у цих особ ознаки екстрапірамідної недостатності (ЕПН) і запропонувати рекомендації для подібної групи ризику. In clinically healthy kinsmen of patients suffering from Parkinson’s disease, we studied the amplitude/frequency characteristics of EMG activity recorded from flexors and extensors of the elbow joint in order to reveal symptoms of extrapyramidal insufficiency (EPI) in these persons and to propose necessary recommendations to such a risk group. We examined four groups of persons: group 1 consisting of 37 healthy kinsmen of patients with clinical diagnosis of Parkinson’s disease; control group 2 consisting of 20 tested persons whose age was analogous to that of persons of group 1; group 3 including 33 Parkinsonian patients; and group 4 of 24 virtually healthy persons of elderly age, i.e., the group considered to be the control one with respect to group 3.